2013
DOI: 10.1177/1359183513483908
|View full text |Cite
|
Sign up to set email alerts
|

The air from outside: Getting to know the world through air practices

Abstract: This article evolves around air: how we experience air, become knowledgeable about our environment through air and include sociality in our actions relating to air. Based on a qualitative study in Denmark about how people use air from the outside and let it into their homes, the article investigates the relation between the air we breathe and learn from and the air we 'perform', such as airing our homes. The study indicates patterns of use that reflect on air as a vital element in our being-in-the-world as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…A previous qualitative study among 29 families showed that window opening was embedded in practices of everyday life such as morning routines or cleaning [31]. It was a way of expressing love and care for the family and the house and connecting to nature.…”
Section: Windows Opening Vs Mechanical Ventilation Systemmentioning
confidence: 99%
“…A previous qualitative study among 29 families showed that window opening was embedded in practices of everyday life such as morning routines or cleaning [31]. It was a way of expressing love and care for the family and the house and connecting to nature.…”
Section: Windows Opening Vs Mechanical Ventilation Systemmentioning
confidence: 99%
“…The residential well-being is significantly dependent on controlling the indoor climate and cannot be isolated from the notion of the 'home,' which is described as a place to rest, a haven, a 'family project,' and an arena for activities (Aune, 2007) and the establishment and negotiation of not only relations (Gram-Hanssen & Bech-Danielsen, 2004) but also practices (Hauge, 2013). Identity, control, freedom and self-determination are vital ingredients of a home (Blunt & Dowling, 2006).…”
Section: Control and The Smart Grid At Homementioning
confidence: 99%
“…The daylight was thus also appreciated for its ability to provide information on the weather and season. The importance of getting knowledge about the world from the natural elements corresponds to other findings on how people use the fresh air from outside in their homes (Hauge 2013a), but is not the focus here; by taking a biomimetic look at the two phenomena the aim is here to show sun and daylight as imbued with sociality by showing people's social, mental, and physiological entanglements with the sun and daylight.…”
Section: Pedermentioning
confidence: 99%
“…The above-mentioned health focus on daylight may in fact be the cause of this neglect, since the health orientation seems to have constituted daylight as a research area for the natural sciences, 3 and for architects 4 and engineers, thereby turning daylight into a phenomenon devoid of sociality. An anthropology of natural elements such as the air, sun, water, fire, earth (Bachelard 1964(Bachelard [1938(Bachelard ], 2002(Bachelard [1943; Ingold 2000Ingold , 2011Ingold and Palsson 2013;Hauge 2013a) would, however, argue for the need to investigate the social qualities of the particular phenomenon and the potentially important insights from how people live with and through these natural elements and use them in their daily lives, and what they say, feel, and think about them. Despite this, people's entanglements with daylight, their thoughts, feelings, and specific actions, such as how to avoid glare from the sun, what they do to let daylight into their homes, their joy from seeing a sunrise from the kitchen window or feeling the warmth from sitting in a sunny window, have so far been neglected.…”
Section: Lives Under the Sun The Sensory Qualities Of Daylight In Desmentioning
confidence: 99%
See 1 more Smart Citation